O indígena no livro didático de história (2013-2014) - Souza, Flaviane Patrício da Silva de (Universidade Federal do Tocantins, 2021)
This work aims to present how indigenous people are approached, from law No. 11,645/08, in three high school textbooks approved by the National Plan of the Textbook - PNLD 2014, analyzing the written part and the images. In this analysis we will seek to understand how indigenous peoples are represented in the historical narrative around the colonization process and in the period before the arrival of Europeans in lands of what would become Brazil, observing mainly the cultural aspects, their struggles, resistances and history.